Fiction and philosophy in the Zhuangzi : an introduction to early Chinese Taoist thought - Graziani, Romain; Graziani, Romain (London, England : Zed Books, 2021)
"The Zhuangzi is one of China's greatest literary and philosophical masterpieces, yet its complexities make it a challenging read. This English translation leads you confidently through the comic scenes and virtuoso writing style, introducing all the little stories Zhuangzi invented and unpicking its philosophy through close commentaries and helpful asides. In Graziani's translation, the co-founder of Daoism emerges as a remarkable thinker. It is a must-read for anyone coming to Chinese philosophy or the Zhuangzi for the first time, and one that reminds us of the importance of thinking beyond our limited, everyday perspectives"--
Part 1: Humans Versus Animals : Carving up a Myth in the Kitchens of Power -- Zoocide: Reflections on the Zhuangzi Bestiary -- Part 2: Humans Versus Death -- One Monster, Two Mortals, and Myriad Metamorphoses -- Fun at the Funerals -- Part 3: Humans Versus Heaven : Acesis and Ecstasy -- The Way of True Men.
Revised, updated and partly rewritten version of a book originally written in French and published in 2006 by the publishing house Gallimard for a general readership under the title Fictions philosophiques du Tchouang-tseu.
Includes bibliographical references and index.
Also published in print.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
Mode of access: World Wide Web.
Keywords: Zhuangzi; Chinese philosophy -- To 221 B.C.; Oriental & Indian philosophy; Electronic books